Renewable energy : a very short introduction - Jelley, N. A. 1946- (Very short introductions, 2020)
Energy is vital for a good standard of living, and much of the world's population does not have enough. Affordable and adequate sources of power that do not cause climate change or pollution are crucial; and renewables provide the answer. Wind and solar farms can now provide the cheapest electricity in many parts of the world. Moreover, they could provide all of the world's energy needs. But while market forces are fast helping the transition from fossil fuels to renewables, there are opposing pressures, such as the USA's proposed withdrawal from the Paris Agreement, and the vested interests in fossil fuels. This book describes the main renewable sources of energy- solar, wind, hydropower, and biomass- as well as the less well-developed ones- geothermal, tidal, and wave.